Irisin, a promising adipomyokine, shows low levels in relation to periodontal diseases, unlike visfatin and IL-6 (case-control study) - Salim, Farah Sabah; Saliem, Saif S. (Frontiers in Oral Health, 2025)
IntroductionAdipose tissue releases pro- and anti-inflammatory cytokines and hormones such as irisin, visfatin, and interleukin-6, which may be linked to periodontal diseases.ObjectivesOur study aimed to determine salivary irisin, visfatin, and interleukin-6 levels in gingivitis and periodontitis patients, compare them with healthy periodontal patients, and evaluate the association between these biomarkers.Materials and methodsNinety participants were involved in this case-control study: 30 patients diagnosed with periodontitis (P), 30 patients with gingivitis (G), and 30 periodontally healthy subjects (control; C). The periodontal clinical parameters were documented. The ELISA test examined irisin, visfatin, and interleukin-6 saliva levels. Data were analyzed using SPSS (V.29).ResultsIrisin significantly decreased in gingivitis and periodontitis compared to the control group (p < 0.05). In contrast, gingivitis and periodontitis reported elevated levels of visfatin and interleukin-6 compared to the control group (p < 0.05). Visfatin levels did not significantly change between gingivitis and periodontitis (p > 0.05). All periodontal clinical measures showed a significant negative association with irisin (p < 0.05), except plaque index in the gingivitis group. At the same time, visfatin and interleukin-6 showed significant positive relationships with all clinical periodontal markers (p < 0.05).ConclusionsSalivary irisin levels were reduced in individuals with gingivitis and periodontitis, whereas visfatin and interleukin-6 levels were elevated. These biomarkers may predict susceptibility to periodontal disease.